Regulation of VEGFA, KRAS, and NFE2L2 Oncogenes by MicroRNAs in Head and Neck Cancer - Cuzziol, Caroline Izak (2022)
Mutations and alterations in the expression of VEGFA, KRAS, and NFE2L2 oncogenes play a key role in cancer initiation and progression. These genes are enrolled not only in cell proliferation control, but also in angiogenesis, drug resistance, metastasis, and survival of tumor cells. MicroRNAs (miRNAs) are small, non-coding regulatory RNA molecules that can regulate post-transcriptional expression of multiple target genes. We aimed to investigate if miRNAs hsa-miR-17-5p, hsa-miR-1405p, and hsa-miR-874-3p could interfere in VEGFA, KRAS, and NFE2L2 expression in cell lines derived from head and neck cancer (HNC). FADU (pharyngeal cancer) and HN13 (oral cavity cancer) cell lines were transfected with miR-17-5p, miR-140-5p, and miR-874-3p microRNA mimics. RNA and protein expression analyses revealed that miR-17-5p, miR-140-5p and miR-874-3p overexpression led to a downregulation of VEGFA, KRAS, and NFE2L2 gene expression in both cell lines analyzed. Taken together, our results provide evidence for the establishment of new biomarkers in the diagnosis and treatment of HNC.